Tactile and auditory stimuli can improve the specific physical performance of para-judo athletes with varied origins of visual impairment - Kons, R. L.; Patatas, J. M.; Franchini, E.; Bragança, J. R.; Detanico, D. (Perceptual and Motor Skills, 2023)
Our aim in this study was to compare performance adaptations based on tactile or sonorous stimuli in para-judo athletes with congenital or acquired visual impairment. Twenty judo athletes with a type of visual impairment performed both the adapted Special Judo Fitness Test (SJFT) with tactile and sonorous stimuli and the standard SJFT. We used two-way ANOVA with repeated measurements in the second factor to compare the SJFT performance of athletes with visual impairment between two groups (acquired or congenital) in the two test situations, with the level of significance set at p < .05. Both groups of participants performed better on the adapted SJFT with tactile and sonorous stimuli compared to the standard condition on number of throws (p = .029 and p < .001) and showed lower final and post 1-minute heart rates (HR) (p < .05). There were no group differences in performance on any SJFT adaptations (p > .05). Thus, both SJFT adaptations (tactile and sonorous stimuli) enhanced the judo-specific performance of athletes with both acquired and congenital visual impairments. However, athletes with either origin of impairment showed a better HR in the adaptive tactile stimuli testing compared to the standard SJFT testing condition.